The current “Ibero-Americanization” policy of the Cervantes Institute - Rizzo, María Florencia (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The present work is theoretically inscribed in the glottopolitical approach and is placed in the context of the current language area policy headed by the Spanish State together with other social agents. In order to explore the direction that this policy has recently taken in the field of Spanish as a foreign language, we will analyze the emergence in 2016 of a new exam system, the International Evaluation Service of the Spanish Language, and its inclusion in an action program promoted by the Cervantes Institute with the name of “Ibero-Americanization” in recent years; as a consequence, the relation of forces between the agents that integrate the field of the certification of Spanish as a foreign language has been significantly modified. Finally, in a broader framework, the aforementioned program of the Spanish institution will be linked with a State policy aimed at promoting of the country-brand and rethinking strategies in Spain’s foreign affairs with Latin American countries.